Answer:
(3,4)
Step-by-step explanation:
first you're going to solve the equation -2x
your equation should now be: ![\left \{ {{-2x+3y\\=6} \atop {-2x=2-2y}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B-2x%2B3y%5C%5C%3D6%7D%20%5Catop%20%7B-2x%3D2-2y%7D%7D%20%5Cright.)
next you're going to substitute the given value of -2x into the equation ![-2x+3y=6](https://tex.z-dn.net/?f=-2x%2B3y%3D6)
so your equation should now be: ![2-2y+3y=6](https://tex.z-dn.net/?f=2-2y%2B3y%3D6)
next you're going to solve the equation for y
equation should now be: y=4
than you're going to substitute the given value of y into the equation
×![4](https://tex.z-dn.net/?f=4)
then you're going to solve the equation for x
your equation should now be: x=3
then the possible solution of the system is the order pair: (x,y)=(3,4)